Revolutionizing Medicine: The Promise of Camouflage Nanoparticles - A Review - Mohammed, Vajagathali; Richard, Nikitha Shalom (Current Nanomaterials, 2025)
Camouflage nanoparticles (CNPs) have emerged as a promising paradigm in the realm of disease therapy, offering a distinctive set of properties and versatile applications. These nanoparticles, characterized by their size, typically falling within the range of 1 to 100 nm, hold significant promise for the realms of targeted drug delivery, diagnostics, and imaging. Diverse categories of camouflage nanoparticles, encompassing liposomes, polymeric nanoparticles, and dendrimers, have been under intensive scrutiny for their potential to combat a spectrum of diseases, including neurological disorders, cardiovascular ailments, genetic anomalies, and cancer. These nanoparticles exhibit the remarkable ability to surmount biological barriers, including the formidable blood-brain barrier, thereby facilitating the precise delivery of therapeutic agents to specific cells or tissues. This precision augments drug efficacy while simultaneously mitigating systemic side effects. Nevertheless, challenges persist in the refinement of nanoparticle design, the assurance of long-term safety, and the pursuit of scalability and cost-effectiveness. Looking ahead, future prospects encompass expanding the purview of disease-specific applications, advancing cutting-edge imaging modalities, crafting multifunctional nanoparticles, and seamlessly integrating nascent technologies. With relentless dedication to research and innovation, CNPs hold the potential to metamorphose the landscape of disease therapy, ushering in a new era marked by heightened drug efficacy, diminished side effects, and the realization of personalized medicine paradigms. This review aims to illuminate the burgeoning arena of CNPs in disease therapy, casting a spotlight on their latent potential as a conduit for targeted drug delivery. Through an exploration of their unique attributes, applications, and extant challenges, this review seeks to galvanize further research and development within this propitious domain, ultimately striving to revolutionize disease therapy by aligning it with the tenets of enhanced efficacy, attenuated side effects, and the realization of personalized medicine aspirations.
Keywords: carbon nanotubes